Is sebab Under The Civil Law The Same As Consideration Under The Common Law? - Rusli, Hardijan (LAW REVIEW, 2001)
A contract without " sebab " (cause) or made with a false or illegal cause is not binding or a void contract (article 1320 and 1335 ofKUHPer). Sebab (Indonesian) means a cause and it is a constituent of a valid contract. Under common law system, one of the elements required to be present in a valid contract is consideration. There are three bases for finding a promise to be enforceable (Schaber, et al. Contracts, p 75) i.e.: 1. Because the promise was made for valid consideration;. 2. Because the promisee has detrimentally relied upon the promise (^detrimental reliance) (see Todd v Nicol; 1957 Â SASR 72); 3. Because the promise comes within a statute which makes it enforceable despite the absence of consideration. The promise comes within a statute means that the statute agrees to be enforceable without consideration but only with consideration substitute staled or mentioned on the statute. Reliance upon a promise is a distinct basis for creation of contract rights and duties. It is not dependent upon finding any agreement nor any bargained exchange consideration. Legal historians have found reliance upon a Â promise to be a historical basis for an action of assumpsit. Restatement Second, section 90 (I) provides that a promise which the promisor should reasonably expect to induce action or forbearance on the part of the promisee or a third person and which does induce such action or forbearance is binding if injustice can be avoided only by enforcement of the promise. The detrimental reliance is actually a quasi contract, whose legal relationship is based on unwritten or common law (quantum meruit), not based on a binding contract. Quantum Meruit is an equitable doctrine, based on the concept that no one who benefits by the labor and materials of another should be unjustly enriched thereby; under those circumstances, the law implies a promise to pay a reasonable amount for the labor and materials furnished, even absent a specific contract therefor ( Swiftships, Inc v Burdin, La.App., 338 So.2d 1193, 1195). Consideration is the primary basis for contract enforcement under the common law system. It is a basic necessary element for the existence of a valid contract that is legally binding on the parties. Is the consideration under common law system the same as sebab under civil law system ? To be able to answer this question, first there is a must to know what is consideration and what is sebab ?Â